Urban polycentrism and total-factor energy efficiency: an analysis based on the night light data - Lu, Yuhai; Gong, Mincheng; Lu, Linzhuo; Wang, Yaqin; Wang, Yang (Elsevier Inc., 2024)
Improving energy efficiency is crucial for environmental protection and resource conservation. Considerable urban system distribution is vital to realizing high energy efficiency. However, studies on energy efficiency from this spatial perspective remain limited. Using the Defense Meteorological Satellite Program's Operational Linescan System (DMSP/OLS) and visible infrared imaging radiometer suite (VIIRS) nighttime light data, we measured urban polycentrism (UPC) and employed improved stochastic frontier analysis (SFA) for total-factor energy efficiency (TEE) measurement. Analyzing panel data from 332 prefecture-level cities across 27 provinces of China, we used the spatial economic and threshold models to calculate UPC's impact on TEE and its threshold conditions. The results revealed UPC's effect on TEE and the control variables (economic development, urbanization rate, and industrial structure). The pattern suggests that only when economic development, urbanization rate, and industrial structure reach a certain (range) level in some zones, does the effect change from one condition (inhibition/promotion) to another (promotion/inhibition). Under certain conditions, a win-win situation between UPC and TEE is achieved. Finally, relevant policy recommendations for energy efficiency improvements based on urbanization are discussed. To the best of our knowledge, this is the first study to systematically investigate the impact of UPC on TEE at the city level.